Bertahan Dalam Pencobaan Menurut Yakobus 1:12-15 Dan Refleksi Teologisnya Terhadap Jemaat GKPPD Sangga Beru - Despriana Rismawati Tumangger; Bernhardt Siburian; Nurelni Limbong (Jurnal Teologi Injili dan Pendidikan Agama, 2025)
The aim of this research is to find out how to surviveTemptation According to James 1:12-15 and to know Reflection on surviving trials according to the letter James 1:12-15 towards the Sangga Beru GKPPD Congregation". The research method used used in writing this scientific work is a qualitative method, namely the approach exegesis by Gordon D. Fee. The interpretation method used is of course by using terms and steps for interpreting the Bible, the steps used by the author are: including text, analyzing text, translating text, comparing translations, criticizing apparatus, grammatical and syntactic analysis, data and analysis of historical situations (cultural historical background), results of exegesis, application. The results of the study stated that everyone was able to survive then he will stand the test, and when he has stood the test he will receive the crown of life God promises to whoever loves Him. And when someone experiences temptation, let no one say this is a trial comes from God because God Himself cannot be tempted by evil and God Himself does not tempt anyone, and on the other hand, temptation comes when someone tests himself because has been enticed by evil so that desire has been fertilized and will give birth to sin and sin will bring death in his life, temptation also brings holy life when someone is able to withstand trials and persevere in life. It's the same with the GKPPD Sangga congregation Beru, who was able to withstand trials and persevere, was patient for years when he experienced trials from the outside in the form of a large-scale demolition of the church so that until now it doesn't have one a proper house of worship. Even so, the Sangga Beru GKPPD congregation continued to implement it duties and responsibilities as a Christian congregation that grows and perseveres in fellowship.